2011
DOI: 10.1371/journal.pone.0014822
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Rural-Urban Migration in India: A Cross-Sectional Study

Abstract: BackgroundMigration from rural areas of India contributes to urbanisation and lifestyle change, and dietary changes may increase the risk of obesity and chronic diseases. We tested the hypothesis that rural-to-urban migrants have different macronutrient and food group intake to rural non-migrants, and that migrants have a diet more similar to urban non-migrants.Methods and findingsThe diets of migrants of rural origin, their rural dwelling sibs, and those of urban origin together with their urban dwelling sibs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 41 publications
(33 reference statements)
5
75
1
5
Order By: Relevance
“…Similar to the present findings, previous studies also reported that the total fat intake was higher in urban (48 g/day) compared with rural (36 g/day) areas (Bowen et al 2011;NSSO 2007). Computations also suggest that 25% of all available fat is consumed by the rural population, while 40% of all edible fat available in India is being consumed by 5% of the total population (i.e., 20% of the urban population that constitutes the "urban-rich") (Shetty 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the present findings, previous studies also reported that the total fat intake was higher in urban (48 g/day) compared with rural (36 g/day) areas (Bowen et al 2011;NSSO 2007). Computations also suggest that 25% of all available fat is consumed by the rural population, while 40% of all edible fat available in India is being consumed by 5% of the total population (i.e., 20% of the urban population that constitutes the "urban-rich") (Shetty 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Many studies provide the data on total fat intake by Indian population (NNMB 1996;NSSO 2001;Pandey et al 2004;NSSO 2007;Bowen et al 2011;Dixit and Das 2012). However, data on intake of the type of fat/oil and individual fatty acids is scanty (Goyal, Sadana, and Verma 2005;Gupta, Songra, and Gupta 1997;Kaur and Hira 1997).…”
mentioning
confidence: 99%
“…Migrant women had similar proportions of energy from saturated fat as rural women. 15 In spite that measuring parameter were different, it appears that macro nutrient intake have been more than the observed value in present study.…”
Section: Discussioncontrasting
confidence: 71%
“…In India, adults with higher BMI are perceived to be at higher levels of SES. Individuals with higher income are more likely to afford and consume energy-dense diets and are less likely to be physically active [21, 44]; thus increasing the likelihood of developing obesity [45]. In our study, people with higher BMI (and diabetes) were more likely to be urban residents, rural-to-urban migrants, or urban-to-urban migrants.…”
Section: Discussionmentioning
confidence: 75%